2015
DOI: 10.7863/ultra.34.4.655
|View full text |Cite
|
Sign up to set email alerts
|

Sonographic Evaluation of Hydronephrosis in the Pediatric Population

Abstract: Hydration does have a substantial effect on the anteroposterior diameter, but it does not correlate with a substantial effect on the SFU grade; therefore, well-tempered sonography seems unnecessary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…It has been postulated that semi-automated quantitative analysis of US images in HN kidneys may have a potential clinical utility, reducing up to 62% of DRS ( Cerrolaza et al, 2016 ). Other studies have shown good correlation between sonographic findings such as grade of hydronephrosis and ureteral jets pattern and DRF, suggesting a possible role for such parameters in the long-term monitoring of these patients ( De Bessa Jr et al, 2008 ; Erickson et al, 2007 ; Shapiro et al, 2008 ; Tekgul et al, 2012 ; Walker et al, 2015 ).…”
Section: Introductionmentioning
confidence: 78%
“…It has been postulated that semi-automated quantitative analysis of US images in HN kidneys may have a potential clinical utility, reducing up to 62% of DRS ( Cerrolaza et al, 2016 ). Other studies have shown good correlation between sonographic findings such as grade of hydronephrosis and ureteral jets pattern and DRF, suggesting a possible role for such parameters in the long-term monitoring of these patients ( De Bessa Jr et al, 2008 ; Erickson et al, 2007 ; Shapiro et al, 2008 ; Tekgul et al, 2012 ; Walker et al, 2015 ).…”
Section: Introductionmentioning
confidence: 78%
“…APD and PT were the most commonly used sonographic variables to assess the severity of hydronephrosis [19, 20]. Preoperative APD and PT were considered to predict the improvement of renal function after pyeloplasty in Helmy’s study [21].…”
Section: Discussionmentioning
confidence: 99%
“…As an accessible, inexpensive, and initial method, ultrasonography was used in both study groups, with indications varying according to the time of diagnosis. Compared to other series, ultrasonography continues to be the most useful diagnostic method and the one with the most significant impact on timely detection at prenatal age, thus providing a more timely intervention that impacts the morphological recovery of the renal unit 8,10,15,16 . The hydronephrosis severity scale applied was the same reported in other case series, which delimits the ideal candidate for surgical management from the morphological point of view, regardless of age and time of diagnosis 6 .…”
Section: Discussionmentioning
confidence: 99%
“…Postnatal pathology was detected in only 12% of children with isolated urinary tract dilation during the second trimester of pregnancy; however, it was present in 40% of those with dilation observed during the second and third trimesters of pregnancy 9 . In general, earlier and more frequent postnatal evaluation is recommended in patients with moderate and severe hydronephrosis (SFU grade III and IV) than those with mild dilatation (SFU grade I and II), as moderate and severe cases are associated with an estimated 5-50% risk of requiring surgical intervention 10 . In children with mild hydronephrosis, a functional study by nuclear renography is not imperative to perform.…”
Section: Introductionmentioning
confidence: 99%